A case study of carbon emissions from logistic activities during supply chain disruptions - Siti Zubaidah Amiruddin,; Hawa Hishamuddin,; Noraida Azura Darom,; Hilmi Hisyam Naimin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Supply chain disruptions have significant negative effects on logistics operations, in which recovery actions could in turn affect the environment if certain green precautions are not undertaken. The objective of this research is to assess the effect of disruption on carbon emissions from logistics activities in the supply chain. A case study was carried out in this study to identify the factors of supply chain disruptions that affect logistics operations, and investigate the impact of the disruptions on the environment. Data collection using the Fuel Monitor application and real disruption data from a selected company were used to quantify the carbon emissions during disruption and non-disruption scenarios. Analysis of the study found that carbon emissions during disruption events increased to approximately 18 – 20 % as compared to normal operations. This is due to the increase in travelling distance in order to fulfill customer backorders during the disruption occurrence. The carbon emission amount was slightly higher when using fuel consumption as reference data in comparison to distance travelled, as fuel consumption takes into account the driving behaviour and efficiency of the truck engines. This study is useful for analyzing the impact of supply chain disruptions on the environment, particularly from the post-disruption recovery decisions.